Corruption & State Capture: What Can Citizens Do? - Bracking, Sarah (Daedalus, 2018)
Given South Africa's recent history of corrupt state capture, the country faces two possible futures: a further decline into spoils politics or a return to an improved constitutional democracy. This essay argues that the latter is more likely in the long run, but is by no means guaranteed. Achieving such a future requires public administrators, citizens, the private sector, and top lawmakers to insist on a public-focused social order. This essay suggests that a coalition of anticorruption agents must be built across the public and private sectors, and that this effort will be successful to the extent that it can link people across traditional class and race divides.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE2Mi9kYWVkX2FfMDA1MDk